Upregulation of α3β1-Integrin in Podocytes in Early-Stage Diabetic Nephropathy - Kaichiro Sawada; Masao Toyoda; Noriko Kaneyama; Sawako Shiraiwa; Hitomi Moriya; Han Miyatake; Eitaro Tanaka; Naoyuki Yamamoto; Masaaki Miyauchi; Moritsugu Kimura; Takehiko Wada; Masafumi Fukagawa (Journal of Diabetes Research)
Background. Podocyte injury plays an important role in the onset and progression of diabetic nephropathy (DN). Downregulation of α3β1-integrin expression in podocytes is thought to be associated with podocyte detachment from the glomerular basement membrane, although the mechanisms remain obscure. To determine the mechanism of podocyte detachment, we analyzed the expression levels of α3β1-integrin in podocytes in early and advanced stages of DN. Methods. Surgical specimens from DN patients were examined by in situ hybridization, and the expression levels of α3- and β1-integrin subunits in glomeruli of early (n=6) and advanced (n=8) stages were compared with those of normal glomeruli (n=5). Heat-sensitive mouse podocytes (HSMP) were cultured with TGF-β1 to reproduce the microenvironment of glomeruli of DN, and the expression levels of integrin subunits and the properties of migration and attachment were examined. Results. Podocytes of early-stage DN showed upregulation of α3- and β1-integrin expression while those of advanced stage showed downregulation. Real-time PCR indicated a tendency for upregulation of α3- and β1-integrin in HSMP cultured with TGF-β1. TGF-β1-stimulated HSMP also showed enhanced in vitro migration and attachment on collagen substrate. Conclusions. The results suggested that podocyte detachment during early stage of DN is mediated through upregulation of α3β1-integrin.